Meeting Global Challenges: German-U.S. Innovation Policy: Summary of a Symposium - National Research Council (The National Academies Press, 2012)
While nations have always competed for territory, mineral riches, water, and other physical assets, they compete most vigorously today for technology-based innovations and the value that flows from them. Much of this value is based on creating scientific knowledge and transforming it into new products and services for the market. This process of innovation is complex and interdisciplinary. Sometimes it draws on the genius of individuals, but even then it requires sustained collective effort, often underpinned by significant national investments. Capturing the value of these investments to spur domestic economic growth and employment is a challenge in a world where the outputs of innovation disseminate rapidly. Those equipped to understand, apply, and profit from new knowledge and technical advances are increasingly able to capture the long-term economic benefits of growth and employment. In response to this new, more distributed innovation paradigm, the National Academies Board on Science, Technology, and Economic Policy (STEP) convened leading academics, business leaders, and senior policymakers from Germany and the United States to examine the strengths and challenges of their innovation systems. More specifically, they met to compare their respective approaches to innovation, to learn from their counterparts about best practices and shared challenges, and to identify cooperative opportunities. The symposium was held in Berlin and organized jointly by the German Institute for Economic Research (DIW) and the U.S. National Academies with support of the German Federal Ministry for Education and Research (BMBF) and the American Embassy in Berlin. Both U.S. and German participants described common challenges on a wide variety of issues ranging from energy security and climate change to low-emissions transportation, early-stage financing, and workforce training. While recognizing their differences in approach to these challenges, participants on both sides drew out valuable lessons from each other's policies and practices. Participants were also aware of the need to adapt to a new global environment where many countries have focused new policy measures and new resources to support innovative firms and promising industries. Meeting Global Challenges: U.S.-German Innovation Policy reviews the participants meeting and sets goals and recommendations for future policy.

The Role of Environmental NGOs: Russian Challenges, American Lessons: Proceedings of a Workshop - National Research Council (The National Academies Press, 2001)
An NRC committee was established to work with a Russian counterpart group in conducting a workshop in Moscow on the effectiveness of Russian environmental NGOs in environmental decision-making and prepared proceedings of this workshop, highlighting the successes and difficulties faced by NGOs in Russia and the United States.

An Evaluation of the System of Central Financial Control of Research in State Governments: Bulletin of the National Research Council - National Research Council (The National Academies Press, 1924)

The National Academy of Sciences: The First Hundred Years, 1863-1963 - National Academy of Sciences (The National Academies Press, 1978)
Among the oldest and most enduring of American institutions are those that have been devoted to the encouragement of the arts and the sciences. During the nineteenth century, a great many scientific societies came and went, and a few in individual disciplines achieved permanence. But the century also witnessed the founding of three major organizations with broadly interdisciplinary interests: the Smithsonian Institution in 1846; the Association of American Geologists and Naturalists, which in 1848 became the American Association for the Promotion (later, Advancement) of Science; and the National Academy of Sciences in 1863. The founding of the National Academy of Sciences represented a momentous event in the history of science in the United States. Its establishment in the midst of a great civil war was fortuitous, perhaps, and its early existence precarious; and in this it mirrored the state of science at that time. The antecedents of the new organization in American science were the national academies in Great Britain and on the Continent, whose membership included the principal men of science of the realm. The chartering of academies under the auspices of a sovereign lent the prestige and elements of support and permanence the scientists sought, and in return they made their scientific talents and counsel available to the state. The National Academy of Sciences: The First Hundred Years, 1863-1963 describes the National Academies from inception through the beginning of the space age. The book describes the Academies' work through different periods in history, including the Postbellum years, World War I, the Great Depression, and World War II.

Culture Matters: International Research Collaboration in a Changing World: Summary of a Workshop - National Academy of Sciences; National Academy of Engineering; Institute of Medicine
In an increasingly interconnected world, science and technology research often transects international boundaries and involves researchers from multiple nations. This paradigm provides both new opportunities and new challenges. As science and technology capabilities grow around the world, United States-based organizations are finding that international collaborations and partnerships provide unique opportunities to enhance research and training. At the same time, enhancing international collaboration requires recognition of differences in culture, legitimate national security needs, and critical needs in education and training. Culture Matters is the summary of a workshop convened by the Government-University-Industry Research Roundtable (GUIRR) in July 2013 to address how culture and cultural perception influence and impact the process by which research agreements are made and negotiated across international boundaries. In this workshop, \

Swords into Market Shares: Technology, Economics, and Security in the New Russia - Glenn E. Schweitzer
While researching this book, Glenn Schweitzer met four Moscow physicists who were trying to license Russian technology to western firms for product manufacture. During the worst times, they were reduced to driving taxis to keep things afloat. He asked them, will technological innovation have a discernible impact on the Russian economy in the coming decade? No, was the immediate reply. Are they right? In Swords into Market Shares, Schweitzer examines the roots of such pessimism and the prospects for Russia to prosper from its technology in the post-Soviet world. He explores the different visions of prosperity held by entrepreneurs, technologists, and government officials and goes on to examine the barriers to progress as Russia struggles to build a viable technology industry on its own terms. In accessible language, this book talks about technology's place within Russia's economy and its research and development infrastructure. Schweitzer looks at the impact of the Soviet legacy2014central planning, lack of priorities, scant incentives for personal initiative2014and the aftermath of the Russian financial meltdown of 1998. He also reviews the experiences of American companies that have invested in Russian technology and examines the results of pressure to reform according to the economic model of the West. Schweitzer goes on to document the problems of economic crime and government corruption, which plague activities designed to generate income in Russia. He discusses the lack of protection for intellectual property and taxation issues that stand in the way of technological innovation. The book looks at the impact of the \

The Pervasive Role of Science, Technology, and Health in Foreign Policy: Imperatives for the Department of State - National Research Council (The National Academies Press, 1999)
Issues involving science, technology, and health (STH) have moved to the forefront of the international diplomatic agenda. Other vital issues linked to technological developments pervade longer-range foreign policy concerns. Thus, STH considerations are often central to the Department of State's bilateral and multilateral interactions with other governments. STH aspects play a large role in discussions of such critical topics as nuclear nonproliferation, use of outer space, population growth, adequate and safe food supply, climate change, infectious diseases, energy resources, and competitiveness of industrial technologies. In addressing these issues, expert STH knowledge is essential to the anticipation and resolution of problems and to the achievement of foreign policy goals. The Department, recognizing that it requires strengthened capabilities to address such an array of topics, asked for suggestions by the National Research Council as to how it could better deal with foreign policy issues with STH content.

Science of Science and Innovation Policy: Principal Investigators' Conference Summary - National Research Council (The National Academies Press, 2014)
The National Science Foundation developed the Science of Science and Innovation Policy program (SciSIP) in 2006 to fund basic and applied research that bears on and can help guide public- and private-sector policy making for science and innovation. By design, SciSIP has engaged researchers from many domains in the development of a community of practice who work together to continually develop frameworks, tools, and datasets for implementing science and innovation policy. Since its inception, the SciSIP program has funded more than 150 researchers and their graduate students. The program also contributed to the initiation of the STAR METRICS (Science and Technology for America's Reinvestment: Measuring the Effect of Research on Innovation, Competitiveness and Science) program, a collaborative effort between the National Science Foundation and the National Institutes of Health. The STAR METRICS program develops tools and mechanisms for measuring federal expenditures on scientific activities, with particular focus on quantifying productivity and employment outcomes. Science of Science and Innovation Policy summarizes a public conference convened by the Committee on National Statistics of the National Academy of Sciences\/National Research Council to present research funded by SciSIP and foster intellectual exchange among funded researchers, science, technology, and innovation policy practitioners, and other members of the science community. The conference highlighted advances in the emerging field of the science of science and innovation policy, in particular, models, frameworks, tools, and datasets comprising the evidentiary basis for science and innovation policy. This report focuses on return on investment models; organizational structures that foster accelerated scientific productivity; linkages between commercialized scientific knowledge and job creation; the roles of universities and government in technology transfer and innovation; technology diffusion and economic growth; non-economic impacts of science and innovation expenditures; regional and global networks of knowledge generation and innovation; mechanisms for encouraging creativity and measuring outputs and outcomes from transformative research; and development, manipulation and visualization of data representing scientific activities.

Headline News, Science Views II - National Research Council
Why all the talk about biodiversity? Is malaria really making a comeback? Just what are computer viruses? Many Americans are confused about these and other issues involving science, technology, and health care. But they lack the time or technical background to read scientific reports. Headline News, Science Views II provides short, readable answers directly from the experts. Leading scientists, engineers, and others discuss today's issues in language that is understandable and compelling2014without jargon. This engaging book \

Finding Common Ground: U.S. Export Controls in a Changed Global Environment, Commissioned Papers (The National Academies Press, 1991)

Headline News, Science Views - National Academy of Sciences; National Research Council
Many Americans want information on how to eat a healthier diet, clean up the environment, or improve their children's education. Yet, all too often, people lack the time or background to read scientific reports for answers to these questions. Now, scientists and nonscientists alike will enjoy Headline News, Science Views, a collection of easy-to-read short articles on many of today's most important issues. These readable essays are written by some of the country's leading scientists, engineers, physicians, and other experts. The authors discuss intriguing issues in language that is understandable and compelling...without jargon. Celebrity Bill Cosby contributes an essay on \

21st Century Manufacturing: The Role of the Manufacturing Extension Partnership Program - National Research Council (The National Academies Press, 2013)
The Manufacturing Extension Partnership (MEP) - a program of the U.S. Department of Commerce's National Institute of Standards and Technology - has sought for more than two decades to strengthen American manufacturing. It is a national network of affiliated manufacturing extension centers and field offices located throughout all fifty states and Puerto Rico. Funding for MEP Centers comes from a combination of federal, state, local and private resources. Centers work directly with manufacturing firms in their state or sub-state region. MEP Centers provide expertise, services and assistance directed toward improving growth, supply chain positioning, leveraging emerging technologies, improving manufacturing processes, work force training, and the application and implementation of information in client companies through direct assistance provided by Center staff and from partner organizations and third party consultants. 21st Century Manufacturing seeks to generate a better understanding of the operation, achievements, and challenges of the MEP program in its mission to support, strengthen, and grow U.S. manufacturing. This report identifies and reviews similar national programs from abroad in order to draw on foreign practices, funding levels, and accomplishments as a point of reference and discusses current needs and initiatives in light of the global focus on advanced manufacturing,

Serving Science and Society Into the New Millenium - National Research Council
A symposium titled \

Proceedings of the International Conference on Scientific Information: Two Volumes (The National Academies Press, 1959)
The launch of Sputnik caused a flurry of governmental activity in science information. The 1958 International Conference on Scientific Information (ICSI) was held in Washington from Nov. 16-21, 1958 and sponsored by NSF, NAS, and American Documentation Institute, the predecessor to the American Society for Information Science. In 1959, 20,000 copies of the two volume proceedings were published by NAS and included 75 papers (1600 pages) by dozens of pioneers from seven areas such as: Literature and reference needs of scientists Function and effectiveness of A & I services Effectiveness of Monographs, Compendia, and Specialized Centers Organization of information for storage and search: comparative characteristics of existing systems Organization of information for storage and retrospective search: intellectual problems and equipment considerations Organization of information for storage and retrospective search: possibility for a general theory Responsibilities of Government, Societies, Universities, and industry for improved information services and research. It is now an out of print classic in the field of science information studies.

From Research to Reward: When the Ground Gives Way: Understanding and Predicting Soil Liquefaction Caused by Earthquakes - National Academy of Sciences (The National Academies Press, 2019)

The Impact of Selling the Federal Helium Reserve - National Research Council
The Helium Privatization Act of 1996 (P.L. 104-273) directs the Department of the Interior to begin liquidating the U.S. Federal Helium Reserve by 2005 in a manner consistent with \

Science and Technology in Kazakhstan: Current Status and Future Prospects - National Research Council (The National Academies Press, 2007)
Kazakhstan has an ambitious program to increase its technological competitiveness in the global market place during the next few years, but achieving success will depend in large measure on the effectiveness of upgraded science and technology (S&T) capabilities. This report identifies important opportunities and limitations in the education system, research and development (R&D) institutions, production companies, and service organizations to help governmental organizations in Kazakhstan with strong interests in S&T chart the future course of the country.

Selling the Nation's Helium Reserve - National Research Council (The National Academies Press, 2010)
Helium has long been the subject of public policy deliberation and management, largely because of its many strategic uses and its unusual source-it is a derived product of natural gas and its market has several anomalous characteristics. Shortly after sources of helium were discovered at the beginning of the last century, the U.S. government recognized helium's potential importance to the nation's interests and placed its production and availability under strict governmental control. In the 1960s, helium's strategic value in cold war efforts was reflected in policies that resulted in the accumulation of a large reserve of helium owned by the federal government. The latest manifestation of public policy is expressed in the Helium Privatization Act of 1996 (1996 12 Act), which directs that substantially all of the helium accumulated as a result of those earlier policies be sold off by 2015 at prices sufficient to repay the federal government for its outlays associated with the helium program. The present volume assesses whether the interests of the United States have been well served by the 1996 Act and, in particular, whether selling off the helium reserve has had any adverse effect on U.S. scientific, technical, biomedical, and national security users of helium.

Funding Smithsonian Scientific Research - National Research Council (The National Academies Press, 2003)
This report assesses whether the Smithsonian Institution should continue to receive direct federal appropriations for its scientific research programs or if this funding should be transferred to a peer-reviewed program open to all researchers in another agency. The report concludes that the National Museum of Natural History, the National Zoological Park, and the Smithsonian Center for Materials Research and Education in Suitland should remain exempt from having to compete for federal research dollars because they make unique contributions to the scientific and museum communities. Three other Smithsonian research programs should continue to receive federal funding since they are performing science of the highest quality and already compete for much of their government research money.

Impact of Science and Technology on Regional Economic Development: An Assessment of National Policies Regarding Research and Development in the Context of Regional Economic Development - National Academy of Engineering (The National Academies Press, 1969)